Review of the Brazilian species of Udamopyga Hall, 1938 (Diptera: Sarcophagidae), with the description of a new species and a key to males and females - Santos, Josenilson Rodrigues Dos; de Mello-Patiu, Cátia Antunes (Zootaxa, 2018)
Udamopyga Hall, 1938 sensu stricto previously comprised 20 species: three from the Nearctic Region and 17 from the Neotropics. A comparative morphological study of the seven species so far recorded from Brazil is presented, including a newly described species from the Brazilian Atlantic Forest, Udamopyga squamata sp. nov., with emphasis on the terminalia and the addition of new diagnostic characters. An identification key to the adults of both sexes of these species is provided.